Incidence and Outcome of Acute Kidney Injury in Hospitalised Children - Paudel, Rajan; Shah, Gauri Shankar; Chaudhary, Shipra; Dharel, Dinesh; Timilsina, Anuradha (Journal of Nepal Paediatric Society, 2021)
Introduction: Acute kidney injury (AKI) is common in hospitalised children with adverse short and long term outcomes. Detection of the incidence, etiological profile and outcome of AKI is important for starting preventive and therapeutic modalities. This study aimed to determine the incidence, etiology and short term outcome of AKI at a tertiary centre in Eastern Nepal. Methods: A prospective observational study was conducted in children from two months to 14 years of age admitted in paediatric wards and paediatric intensive care unit (PICU) of a tertiary centre of Eastern Nepal. AKI was defined according to pRIFLE criteria. Results: From May 2015 to March 2016, 942 patients enrolled in Paediatric wards and PICU were evaluated. The overall incidence of AKI was found to be 5.9% and 18.23% in patients admitted in PICU. AKI was commonest among cases having infectious etiology compromising 73.2% (n = 41), 17.85% (n = 10) due to primary renal disease, 5.35% (n = 3) secondary to congenital heart disease, and 3.57% due to other causes. Among AKI patients, 55.4% (n = 31) required inotropic support, 33.9% (n = 19) required mechanical ventilation while 5.36% (n = 3) underwent dialysis. Out of 56 AKI patients 71.4% (n = 40) had improved clinical outcome and 28.6% (n = 16) expired. Patient with AKI had significant longer duration of hospital stay as compared to non AKI (Seven days vs. three days, p < 0.001). Mortality was high among AKI patients on injury and failure stage (p = 0.003) and those requiring mechanical ventilation and inotropic support (p < 0.001). Conclusions: The incidence of AKI was found to be high in paediatric patients. Presence of AKI increased the duration of hospital stay and mortality in hospitalised children often requiring mechanical ventilation and inotropic support.